Self-perceived and actual ability in the functional reach test in patients with Parkinson’s disease - Ryckewaert, Gilles; Luyat, Marion; Rambour, Melanie; Tard, Céline; Noël, Myriam; Defebvre, Luc; Delval, Arnaud (Neuroscience letters, 2015)
•Differences between self-perceived and actual ability to reach an object could lead to falls in PD patients.•Functional reach test performance was altered in PD patients.•Antero-posterior CoP displacement was reduced in PD and elderly subjects.•Ability to estimate self-performance was preserved in PD patients and was not linked to future falls. Falls frequently occur during daily activities such as reaching for an object in patients with Parkinson’s disease (PD). Misjudgment is also reported to be one of the circumstances that lead to falls. The functional reach test is an indicator of dynamic balance. The primary objective was to establish whether there is a difference between self-perceived and actual ability to perform the functional reach test in patients with PD who have never fallen. Three groups of participants (all with no history of falls) were studied: young adults, elderly adults and PD patients. The participants first estimated their maximum reaching distance (but without performing the action, i.e. as a motor imagery task) and then actually performed the functional reach test (i.e. as a motor task). No significant overestimation or underestimation was observed. The reaching distance was lower in PD than in the two other groups. There were no differences between PD patients and elderly adults in terms of the forward centre of pressure displacement. Seven PD patients reported a fall in the year following the experiment. The fallers had a longer history of disease. Finally, PD patients adequately estimated their ability in the functional reach test and did not adopt an “at risk” strategy and appeared to be quite conservative (as were healthy elderly adults) in their postural control behavior. Ability to estimate self-performance is preserved in PD patients with no clinical impairments of postural control although they are at risk of future falls.